2017
DOI: 10.3847/1538-4357/aa816d
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Mass Function in the Nearest Strong Lenses from SNELLS: Assessing the Consistency of Lensing, Dynamical, and Spectroscopic Constraints

Abstract: (2017) 'The initial mass function in the nearest strong lenses from SNELLS : assessing the consistency of lensing, dynamical, and spectroscopic constraints.', The astrophysical journal., 845 (2). p. 157.Further information on publisher's website:https://doi.org/10.3847/1538-4357/aa816dPublisher's copyright statement: c 2017. The American Astronomical Society. All rights reserved. Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 91 publications
5
82
2
1
Order By: Relevance
“…Furthermore, there are still unexplained complications in the emerging picture of IMF variability. Newman et al (2016) demonstrated that even high-velocity dispersion ETGs can have Kroupa (2001;MW) IMFs, and, furthermore, it is not yet clear how IMF variability conforms to the expectations from chemical evolution and star formation measurements (e.g., Martín-Navarro 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are still unexplained complications in the emerging picture of IMF variability. Newman et al (2016) demonstrated that even high-velocity dispersion ETGs can have Kroupa (2001;MW) IMFs, and, furthermore, it is not yet clear how IMF variability conforms to the expectations from chemical evolution and star formation measurements (e.g., Martín-Navarro 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They find that while both methods agree in suggesting a global bottomheaviness of the IMF over their respective observational samples, a detailed comparison for the giant ellipticals in common between the samples shows large systematics and lack of agreement, however, thus casting doubts on the individual results. Furthermore, Newman et al (2017) perform a similar comparison between dynamical, spectroscopic, and, in addition, lensing-based mass estimates for a sample of three nearby giant ellipticals. They show that if the underlying IMF is parametrized as a single or broken power law, the results for the three methods disagree for two out of the three galaxies in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al (2015b) found that for two strong-lens ETGs in the SINFONI Nearby Elliptical Lens Locator Survey (SNELLS) with σ∼300 km s −1 a bottom-heavy IMF is ruled out in favor of a Kroupa IMF, but find their 1.14 Na I μm index strengths to suggest that they have bottom-heavy IMFs (Smith et al 2015a). Recently Newman et al (2016) compared lensing, dynamical, and SPS techniques for inferring the IMF of these SNELLS galaxies, finding that the SPS stellar mass-to-light ratios exceed the total lens mass-to-light ratio, and that there is even a significant discrepancy between the lensing and dynamical masses. Newman et al (2016) discuss several possibilities for the origin of these tensions, but this study suggests that there could be systematic errors in at least one of the techniques used to probe the IMF of ETGs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Newman et al (2016) compared lensing, dynamical, and SPS techniques for inferring the IMF of these SNELLS galaxies, finding that the SPS stellar mass-to-light ratios exceed the total lens mass-to-light ratio, and that there is even a significant discrepancy between the lensing and dynamical masses. Newman et al (2016) discuss several possibilities for the origin of these tensions, but this study suggests that there could be systematic errors in at least one of the techniques used to probe the IMF of ETGs.…”
Section: Introductionmentioning
confidence: 99%